Employees provident fund (EPF) / Zarith Eleena Za'aba - Za'aba, Zarith Eleena (2014)
The Employees Provident Fund (EPF) is the place that I choose for my practical training for 6 weeks. As we know, Employees Provident Fund is the well known organizations to the Malaysian Citizens. The Employees Provident Fund (EPF) is Malaysia’s premier retirement savings fund providing basic financial security for retirement. Employees Provident Fund (EPF) established in 1951. The fund is one of the world’s oldest and among the largest with total investment assets of RM586.66 billion as at end 2013. Membership ofthe Fund grows by the year and today stands at 13.92 million, of whom 6.53 million are active members (KWSP, 2010).